Overexpression of lncRNA MT1JP Mediates Apoptosis and Migration of Hepatocellular Carcinoma Cells by Regulating miR-24-3p - Shan, Qiu-Li (Cancer Manag Res, 2020)
OBJECTIVE: This study aimed to determine the effects of the long non-coding (lnc) RNA MT1JP on the apoptosis and migration of hepatocellular carcinoma cells. PATIENTS AND METHODS: Patients with liver cancer admitted to the Second People’s Hospital of Liaocheng were included in this study. We transfected hepatocellular carcinoma cells with MT1JP and miR-24-3p and assessed their expression and effects on apoptosis and migration. Correlations were verified using a dual-luciferase reporter and RNA-binding protein coimmunoprecipitation. RESULTS: The expression of MT1JP was downregulated (P < 0.05), whereas that of miR-24-3p was upregulated in liver cancer. Serum MT1JP levels were correlated with tumor size, alpha-fetoprotein (AFP), TNM stage, differentiation, and lymph node metastasis. Both MT1JP overexpression and miR-24-3p inhibition inhibited cellular proliferation and migration and increased apoptosis rates. They significantly downregulated expression of the cell migration-associated proteins matrix metalloproteinase -2, -9 (MMP-2, MMP-9) (P < 0.05). They upregulated the expression of Bcl-2-related X protein (Bax) and cysteinyl aspartate-specific proteinases (Caspase-3 and -9) proteins that are involved in apoptosis. They decreased expression of B-cell lymphoma/leukemia-2 (Bcl-2; P < 0.05). A target relationship between MT1JP and miR-24-3p was identified using dual-luciferase gene reporter assays and RNA-binding protein coimmunoprecipitations. MT1JP overexpression significantly downregulated miR-24-3p expression (P < 0.05). MT1JP and miR-24-3p expression were negatively correlated in liver cancer tissues (r = −0.561, P < 0.001; Pearson χ(2) tests). Rescue experiments showed that upregulating miR-24-3p expression could counteract MT1JP overexpression in hepatocellular carcinoma cells. CONCLUSION: MT1JP, even when expressed at low levels, participates in the proliferation, apoptosis, and migration of liver cancer cells by regulating miR-24-3p.